IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DI DALAM KEPEMIMPINAN KEPALA SEKOLAH - Bazargan (UNISAN JURNAL, 2024)
In an educational institution organization, namely a school, the principal is the leader who will lead the school towards its goals which lead to achieving school quality in accordance with what has been targeted. The school principal is an important individual in running a school-based management system where he is given greater autonomy in implementing and making policies related to improving the quality of learning. This research uses qualitative techniques with a descriptive model. The subjects in this research are the Principal and Teachers at SMA 1 Pesisir Selatan, Pesisir Barat Regency, Lampung. Researchers used triangulation techniques to check the validity of the data. The results of this research, SMA 1 Pesisir Selatan Regency Pesisir Barat Lampung used a democratic leadership style. The School Based Management Model is implemented in accordance with school needs and government regulations. Principals implement management strategies that give schools more autonomy and flexibility while encouraging direct involvement of students and the community in improving school quality. Limited funds and facilities/infrastructure hamper the implementation of SBM, and community involvement has not been maximized. Keywords: SBM, Leadership, Principal